Induction of expression of monocyte interleukin 1 by Hageman factor (factor XII). - Toossi, Z (1992)
The results reported here indicate that activated species of Hageman factor (HF, factor XII), a protein that mediates blood clotting, fibrinolysis, and activation of the complement cascade, induce elaboration of interleukin 1 (IL-1) by human monocytes. Augmentation of IL-1 production in mononuclear cell cultures was observed when HF was present along with lipopolysaccharide (LPS) but was not observed with HF alone. Furthermore, antiserum to HF abrogated the enhancement of IL-1 in cultures containing HF and LPS. Total IL-1 activity, which represents secreted and cell-associated IL-1, was enhanced in LPS-stimulated mononuclear cultures by HF. In the absence of LPS, the initial activation product of HF, HFa, which contains the serine protease enzyme activity and the surface-binding domains of the protein, induced IL-1 beta protein and mRNA. In the presence of LPS, the enzymatic moiety (HFf), which is also contained in HF and HFa, amplified IL-1 production. Induction and amplification of monocyte IL-1 by HF provides further evidence for establishing a role for HF in the acute-phase reaction and the cellular immune response.